Clinical Characteristics and Antimicrobial Susceptibility of Mycobacterium intracellulare and Mycobacterium abscessus Pulmonary Diseases: A Retrospective Study - Dongping Wang; Wenhong Lin; Hongyan Cheng; Xundi Bao; Dongfang Xu; Suo Liang; Yue Jiang; Chao Wang (Canadian Journal of Infectious Diseases and Medical Microbiology)
The incidence of nontuberculous mycobacteria (NTM) diseases is increasing every year. The present study was performed to investigate the clinical characteristics, CT findings, and drug susceptibility test (DST) results of patients diagnosed with M. intracellulare or M. abscessus nontuberculous mycobacterial pulmonary disease (NTMPD). This retrospective study included patients diagnosed with NTMPD due to M. intracellulare or M. abscessus for the first time at Anhui Chest Hospital between 01/2019 and 12/2021. The patients were grouped as M. intracellulare-NTMPD group or M. abscessus-NTMPD group. Clinical features, imaging data and DST data, were collected. Patients with M. intracellulare infection had a higher rate of acid-fast smears (66.1% vs. 45.2%, P=0.032) and a higher rate of cavitation based on pulmonary imaging (49.6% vs. 19.4%, P=0.002) than patients with M. abscessus infection, but both groups had negative TB-RNA and GeneXpert results, with no other characteristics significant differences. The results of DST showed that M. intracellulare had high susceptibility rate to moxifloxacin (95.9%), amikacin (90.1%), clarithromycin (91.7%), and rifabutin (90.1%). M. abscessus had the highest susceptibility rate to amikacin (71.0%) and clarithromycin (71.0%). The clinical features of M. intracellulare pneumopathy and M. abscessus pneumopathy are highly similar. It may be easily misdiagnosed, and therefore, early strain identification is necessary. M. intracellulare has a high susceptibility rate to moxifloxacin, amikacin, clarithromycin, and rifabutin, while M. abscessus has the highest susceptibility rate to amikacin and clarithromycin. This study provides an important clinical basis for improving the management of NTMPD.